2009
DOI: 10.1177/1354068809342526
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Political Party Leadership in Canada

Abstract: In this article, we compare the experiences of male and female party leaders at the provincial and federal levels in Canada between 1980 and 2005 and test several hypotheses regarding gender and party leadership. The Canadian case provides an excellent case study given the relatively large number of women (21 in total) who held the position of party leader during the time period in question. The case study reveals that major parties are less likely to elect women as their leaders, while parties on the ideologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 15 publications
1
41
0
2
Order By: Relevance
“…The scarce literature on reselection at the top executive level indicates that incumbency is the most prominent factor. This notwithstanding, research on gender and political parties has shown that female party leaders have a greater likelihood of stepping down when their parties lose vote share (O'Brien 2015;O'Neill & Stewart 2009). Loser candidates also tend to get another shot when being the party leader (Astudillo 2015).…”
Section: Reselectionmentioning
confidence: 99%
“…The scarce literature on reselection at the top executive level indicates that incumbency is the most prominent factor. This notwithstanding, research on gender and political parties has shown that female party leaders have a greater likelihood of stepping down when their parties lose vote share (O'Brien 2015;O'Neill & Stewart 2009). Loser candidates also tend to get another shot when being the party leader (Astudillo 2015).…”
Section: Reselectionmentioning
confidence: 99%
“…In contrast to this wide body of research, and despite the important role played by party leaders, to date there has been comparatively little research on women's access to these posts. The research that aims to make more general claims examines variation within a single country (O'Neill and Stewart 2009) or across a limited set of states in which women rarely come to power (Cross and Blais 2012b). The research that aims to make more general claims examines variation within a single country (O'Neill and Stewart 2009) or across a limited set of states in which women rarely come to power (Cross and Blais 2012b).…”
Section: The Importance Of Women's Access To the Party Leadershipmentioning
confidence: 99%
“…In particular, the "firmness of a party's grip on power [in government] or its proximity to power in opposition" has been inversely related to women's leadership success (Bashevkin 2010, 87). Women have thus been most likely to serve as leaders of minor parties (O'Neill and Stewart 2009) and opposition parties that are unlikely to serve in government in the near future (Bashevkin 1993). In fact, Trimble and Arscott (2003) argue that the most common pathway to power for Canadian female party leaders is to take control of "electorally decimated and moribund parties" (77).…”
Section: Hypothesizing About Performance and Women's Entrance Into Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Leftist parties (Socialists and Greens) support egalitarian ideologies and are for ideological reasons more open to marginalized groups in the society (Matland and Studlar 1996). This "women friendly" stance resulted in the recruitment of more women, the placement of more women in winnable positions on their lists (Duverger 1955;Matland and Studlar 1996;Caul 1999;Kittilson 2006), and the promotion of women to their top echelons (O'Neill and Stewart 2009;Kittilson 2013). They are also more likely to adopt quotas for female representation.…”
Section: Politics Groups and Identitiesmentioning
confidence: 99%